2008
DOI: 10.1063/1.2927494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the chemical and electronic structure on the electrical behavior of zirconium oxynitride films

Abstract: This work is devoted to the investigation of decorative zirconium oxynitride, ZrOxNy, films prepared by dc reactive magnetron sputtering, using a 17:3 nitrogen-to-oxygen-ratio gas mixture. The color of the films changed from metallic-like, very bright yellow pale, and golden yellow, for low gas mixture flows [from 0 to about 9SCCM (SCCM denotes cubic centimeter per minute at STP)] to red brownish for intermediate gas flows (values up to 12SCCM). Associated to this color change there is a significant decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 108 publications
12
66
0
1
Order By: Relevance
“…Fig. 1 shows the XRD pattern of the nanocrystalline thin films of zirconium oxynitride (A, B, C, D and E) deposited in N 2 + Ar mixture with varying oxygen partial pressure at 500 • C. At 2.5% oxygen partial pressure, the (2 2 2) and (4 4 0) peaks of metastable ␥-Zr 2 ON 2 which are also observed by Carvalho et al [8] , along with (1 1 1) peak of m-ZrO 2 are observed. The evolution of (4 0 0), (4 3 1), and (3 1 1) peaks of ␥-Zr 2 ON 2 occurs from 4.0% oxygen partial pressure.…”
Section: Resultssupporting
confidence: 66%
“…Fig. 1 shows the XRD pattern of the nanocrystalline thin films of zirconium oxynitride (A, B, C, D and E) deposited in N 2 + Ar mixture with varying oxygen partial pressure at 500 • C. At 2.5% oxygen partial pressure, the (2 2 2) and (4 4 0) peaks of metastable ␥-Zr 2 ON 2 which are also observed by Carvalho et al [8] , along with (1 1 1) peak of m-ZrO 2 are observed. The evolution of (4 0 0), (4 3 1), and (3 1 1) peaks of ␥-Zr 2 ON 2 occurs from 4.0% oxygen partial pressure.…”
Section: Resultssupporting
confidence: 66%
“…On the other hand, the inverse calibrated phases, measured for the two coatings ZrON1 (o) and ZrON2 (∆) at higher modulation, deviate from the two-layer model to lower values. This behaviour, which is characteristic for a three-layer structure with a thin surface on top of the coating of reduced thermal effusivity, e s < e c , can be explained for the two coatings ZrON1 and ZrON2 by very thin oxide contamination layers just at the surface [4].…”
Section: Theoretical Description Of the Measured Amplitude And Phase mentioning
confidence: 99%
“…4, the coatings ZrON1 and ZrON2 are metal-like coatings with a cubic-type structure, whereas the coatings ZrON3 and ZrON4 have a different crystalline structure characterized by a mixture of two electrically insulating structures: An orthorhombic nitride structure and a cubic oxynitride structure [3]. These differences of composition and structure, which affect all film properties [3,4], are found in the range of intermediate and higher modulation frequencies of the inverse calibrated modulated IR phases ( 1/2 > 150, the inverse calibrated phases measured for the two coatings ZrON3 ( ) and ZrON4 (+) considerably exceed the zero-line (Φ n = 0 deg), showing a behavior which is characteristic for semi-transparent coatings, as observed in fact for these two films in optical measurements carried out by UV-Vis spectrophotometry [3,4]. On the other hand, the inverse calibrated phases, measured for the two coatings ZrON1 (o) and ZrON2 (∆) at higher modulation, deviate from the two-layer model to lower values.…”
Section: Theoretical Description Of the Measured Amplitude And Phase mentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, these thin films also present a good electrical conductivity. Within this type of materials we can quote the nitrides, oxinitrides, carbides and nitrocarbides of the elements of the first transition series [8]. In comparison with the huge number of works on this topic available in the literature, there are very few reports on the preparation of colored oxide thin films which show some absorption in the visible region of the electromagnetic spectra.…”
Section: Introductionmentioning
confidence: 99%